2022
DOI: 10.3389/fneur.2022.890860
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening and gene therapy in SMA: Challenges related to vaccinations

Abstract: Spinal muscular atrophy (SMA) affects one in 7,500–10,000 newborns. Before the era of disease-modifying therapies, it used to be the major genetic cause of mortality in infants. Currently, there are three therapies approved for SMA, including two molecules modifying the splicing of the SMN2 gene and one gene therapy providing a healthy copy of the SMN gene with a viral vector. The best effects of any of these therapies are achieved when the treatment is administered in the presymptomatic stage of the disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
6
0
3
Order By: Relevance
“…This is in line with the observation that early treatment will lessen the severity of the disease. Previous studies have stated that the pharmaceutical treatments for SMA are most effective if administered immediately after or even before the onset of clinical symptoms [ 14 , 36 ]. Therefore, a newborn screening has been proposed to be the most effective way to ensure early diagnosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in line with the observation that early treatment will lessen the severity of the disease. Previous studies have stated that the pharmaceutical treatments for SMA are most effective if administered immediately after or even before the onset of clinical symptoms [ 14 , 36 ]. Therefore, a newborn screening has been proposed to be the most effective way to ensure early diagnosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kotulska et al speculated about the same issue in their review on SMA. Although overall motor development and survival of the pharmaceutically treated SMA patients improved, the patients still developed early-onset scoliosis [ 14 ]. In this study, the amount of fewer gene copies showed a statistical significant correlation with higher kyphotic curve angles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A discussion of the disease and some of the diagnostic issues was published in 2020 and provides information that is potentially useful as screening policies are developed [950]. The Polish Vaccinology Association published the first recommendations for gene therapy for newborns who received live vaccination against tuberculosis, which might be helpful in other countries where live vaccine against tuberculosis is still used [951].…”
mentioning
confidence: 99%